Die pastoor as fluisteraar. Gedagtes oor pastorale identiteit en arbeid na analogie van die perdefluisteraar - Danny Nel (Acta Theologica)
Generally, note have been taken that the work of pastoral care and the pastoral counselor are surrounded by identity issues for the latter part of the previous century and in the first decade of this century. In some circles it is even described as a profession without a place or position, looking and struggling for recognition, experiencing a crisis. In this article some of the reasons underlying these identity issues are mentioned or described. Comparing it with the work of a horse therapist, a horse whisperer, the unique position and emphasis of pastoral counseling and the pastoral counselor are pointed out with specific reference to the use of scripture, shared woundedness, the pastoral relationship, the moments of pastoral silence with distinct meaning and a particular sort of externalization. Keeping this in mind, the pastoral therapist can be still be deemed pastor aeturnus.